2000
DOI: 10.1091/mbc.11.8.2565
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of an SHP-2-Rho Small G Protein Pathway in Hepatocyte Growth Factor/Scatter Factor–induced Cell Scattering

Abstract: Hepatocyte growth factor/scatter factor (HGF/SF) induces cell scattering through the tyrosine kinase-type HGF/SF receptor c-Met. We have previously shown that Rho small G protein (Rho) is involved in the HGF/SF-induced scattering of Madin-Darby canine kidney (MDCK) cells by regulating at least the assembly and disassembly of stress fibers and focal adhesions, but it remains unknown how c-Met regulates Rho activity. We have found here a novel signaling pathway of c-Met consisting of SHP-2-Rho that regulates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 61 publications
3
112
0
Order By: Relevance
“…18, January 2007the activation of receptor binding signaling components in response to HGF but is needed to activate Ras, most likely via the recruitment of Ras into a complex with Sos (or a Shp-2-regulated GEF; Kodama et al, 2000). In agreement with this assumption, ezrin could be coimmunoprecipitated with Sos upon HGF stimulation in 293 cells ( Figure 3D).…”
Section: F-actin Organizes Ras Activationsupporting
confidence: 52%
“…18, January 2007the activation of receptor binding signaling components in response to HGF but is needed to activate Ras, most likely via the recruitment of Ras into a complex with Sos (or a Shp-2-regulated GEF; Kodama et al, 2000). In agreement with this assumption, ezrin could be coimmunoprecipitated with Sos upon HGF stimulation in 293 cells ( Figure 3D).…”
Section: F-actin Organizes Ras Activationsupporting
confidence: 52%
“…These results are consistent with previous reports that showed that SHP2 plays a positive role in fibroblast motility and migration. [23][24][25][26] Thus, interference with SHP2 function might provide a means to inhibit cancer cell metastasis. Unexpectedly, we discovered that EGF can induce translocation of b-catenin to the nucleus in SHP2-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that SHP2 suppresses cell adhesion and enhances motility. [23][24][25][26] We sough to investigate the significance of SHP2 inhibition on breast cancer cells motility and scattering. Initially, this possibility was tested by the monolayer wound-healing assay.…”
Section: Shp2mentioning
confidence: 99%
“…Induction of scattering (37,38) and branching morphogenesis (39) of MDCK epithelial cells by the growth factor HGF/SF have been shown to depend on Shp2 (18,30). Stimulation of MDCK epithelial cells grown on cell culture dishes with HGF/SF results in loss of cell-cell contacts, increased cell motility, and conversion from an epithelial to a fibroblast-like appearance (Fig.…”
Section: Phps1mentioning
confidence: 97%